Kedudukan anak dalam kandungan sebagai ahli waris Dalam perspektif kompilasi hukum islam - Ramadanah, Putra (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
The position of the unborn child as an heir in the positive law that applies in Indonesia is not found a clear rule. In KHI Article 174 paragraph (1) which talks about who is entitled as an heir, the unborn child is not described. While in some conventional fiqh literature, the position of the child in the womb gets a portion of the discussion in the science of inheritance. The formulation of the problem in this thesis is how the status of the unborn child as an heir according to Islamic law, how the position of the unborn child as a surrogate heir in the perspective of Islamic law, how the mechanism of division of the unborn child as a surrogate heir in perspective of Islamic law. This type of research is research using the method of normative juridical approach. Data collection in this study is done through a literature study, where the material or data obtained will be systematically compiled and analyzed using scientific logic procedures that are qualitative in nature. The results of the research are expected to be able to answer the problems researched, and in the end will be able to provide suggestions and solutions to these problems. The results show that the status of the child who is still in the womb as an heir according to Islamic law in conventional jurisprudence is entitled to receive an inheritance if there are reasons for inheritance (marriage, kinship, and freeing slaves). The position of the child in the womb in the Compilation of Islamic Law can be said to have been neglected or forgotten, even though this is a big question that must be resolved now. Neglect of the inheritance of the child in the womb will result in the child will be threatened in the future, not impossible when the child in the womb until birth turns out to be his right as an heir cut off by other relatives. The position of the inheritance of the unborn child as an heir in the legal perspective has legal consequences for theother heirs, including the postponement of the division of inheritance until there is certainty about the sex of the child. The mechanism of division of the inheritance of the unborn child as an heir in the perspective of Islamic law can use 2 (two) ways, namely by waiting after the baby is born. If the other heirs want the division to be done immediately without waiting for the birth of the baby, then the inheritance can be divided by taking into account the baby's share for 1 (one) person, even if it can also be born in twins. Keywords: Children, Content, Successor Heirs.